Energetika dogajanj v ozračju - Rakovec, Jože (Obzornik za matematiko in fiziko, 2008)
In Introduction the energy, released in a moderate shower is compared with the amount of energy, produced in a nuclear power plant - to illustrate how big are the amounts of energy transforms in the atmosphere. In Part I the main energy exchanges from solar into the sensible heat and the latent heat of evaporation, the advection of these across the globe, as well as the release of the latent heat by condensation are presented on the basis of the measured data and the values obtained by meteorological models.
Keywords: energija; latentna toplota; meteorologija; ozračje